Network, Smart and Open Three Keywords for Information Systems Innovation (Lecture Notes in Information Systems and Organisation,, 2018)
This book presents a collection of original research papers addressing the relationship between information systems (IS) and innovation. "Open", "Smart" and "Network" are three keywords that are currently guiding information systems (IS) innovation, enhancing IS potentialities and their ability to support decision-making processes. The book discusses the relevance of these three new concepts in connection with technological and organizational innovations (i.e. cloud, smart technologies and networking), and the role they play in the development of accounting and management information systems. The book's primary aim is to investigate how these innovations could influence information systems (with a particular focus on accounting and management information systems) by enhancing their information potentialities and improv ing accounting methodologies, performance measurement systems, data management, information systems architectures, and external and internal reporting. The book is based on a selection of the best papers-original double-blind reviewed contributions-presented at the 2016 Annual Conference of the Italian Chapter of the Association for Information Systems (AIS).